Pilot turning behavior cognitive load analysis in simulated flight - Zhou, Wen-gang; Yu, Pan-pan; Wu, Liang-hai; Cao, Yu-fei; Zhou, Yue; Yuan, Jia-jun (Frontiers in Neuroscience, 2024)
BackgroundTo identify the cognitive load of different turning tasks in simulated flight, a flight experiment was designed based on real “preliminary screening” training modules for pilots.MethodsHeart Rate Variability (HRV) and flight data were collected during the experiments using a flight simulator and a heart rate sensor bracelet. The turning behaviors in flight were classified into climbing turns, descending turns, and level flight turns. A recognition model for the cognitive load associated with these turning behaviors was developed using machine learning and deep learning algorithms.Resultspnni_20, range_nni, rmssd, sdsd, nni_20, sd1, triangular_index indicators are negatively correlated with different turning load. The LSTM-Attention model excelled in recognizing turning tasks with varying cognitive load, achieving an F1 score of 0.9491.ConclusionSpecific HRV characteristics can be used to analyze cognitive load in different turn-ing tasks, and the LSTM-Attention model can provide references for future studies on the selection characteristics of pilot cognitive load, and offer guidance for pilot training, thus having significant implications for pilot training and flight safety.